Internet Memes In China: Cultural Image Macros of Code-Switching and Homonymy - Aiqing Wang (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2023)
Since China joined the Internet in the late 1980s, production and consumption of online cultural merchandise has been proliferating and permeating every section of society, exemplified by Internet literature, animation, comic and game. Meanwhile, there has emerged a veritable kaleidoscope of memes in China’s cyberspace, which are deployed on social media platforms to convey stances, emotions, humorousness, etc. Nonetheless, as a multi-faceted phenomenon, Internet memes fail to attain deserved academic scrutiny, so in this paper, I investigate one subcategory of memes in China’s cyberspace, viz. cultural memes, focusing on image macros that dynamically integrate visual effects and textual information. The text of cultural image macros can be generated via Chinese-English code-switching in the form of alphabetic words that are either idiomatic or related to Internet buzzwords. Alternatively, cultural image macros in China can be generated via homonymy: the vast majority of homonyms are homophones, while a small proportion of them are homographs. The corresponding images in the memes pertain to the inserted English words or constituents that are substituted, thereby complementing the text and strengthening humorous effects.